PELATIHAN SPORT MASSAGE BAGI MAHASISWA PENDIDIKAN JASMANI UNIVERSITAS MULAWARMAN - Muchamad Samsul Huda; Didik Cahyono; Jupri Jupri (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Based on the theories that have been explained, that the provision / handling by providing massage injury services at this time is very much needed. Due to strenuous exercise and lack of heating can cause injury. With this massage injury training, it has provided knowledge and skills to trainees. So that the participants know the science of sports massage.  By knowing the existing theories about injuries, the types and forms of handling, will minimize the occurrence of anxiety. In addition, with training, provide clear information about the right times for the provision of massage services/ services. With the training that has been implemented, this has had a positive impact on all pesesrta. Starting from the creation of new jobs, providing additional economies, and providing opportunities for participants to dedicate the knowledge that has been obtained to the field and the community.  Some things that can be inferred from the activity of applying masasge skill practicum, in addition to student knowledge increases in applying masasge skills to the wider community. For students to increase knowledge about sports masase therapy both in theory and practice so that it can be applied by students as one of the efforts to improve achievements in the field of sports. And of course the trainees get a deeper knowledge of sports injuries. The knowledge obtained not only in the explanation of materials and theories but also in direct practice is expected to prevent and minimize the occurrence of injuries in sports.